Target-related autobiographical memories affect dietary intake intentions. Issue 10 (26th November 2019) - Merson, Brittany; Pezdek, Kathy
ABSTRACT: Although there is evidence that autobiographical memory (AM) recall impacts behaviour in multiple domains, the mechanisms for this effect are unclear. Two experiments examined how AM Frame and Relatedness to target behaviour affect intention to control future dietary intake. Participants completed an AM task where they recalled success or fail-framed memories of behaviour in the target domain (dietary intake), a related domain (exercise), and an unrelated domain (work). Next they completed questionnaires about attitudes, self-efficacy, and behavioural intention for controlling dietary intake. In Experiment 1, Frame and Relatedness of AMs recalled did not affect attitudes or self-efficacy ratings of controlling dietary intake. However, Related AMs resulted in higher intention ratings to control future dietary intake compared to Unrelated AMs. Experiment 2 replicated these results for attitude and self-efficacy, but showed no effect on behavioural intention. A mini-meta analysis was conducted to clarify the effect of AM recall on intention. This analysis confirmed a significant effect of AM Relatedness on intention ratings (meta-analysis Cohen's d = .25, Z = 2.54, p = .011). These results provide evidence that recalling related AM can affect dietary behaviour intentions directly, without changes attitudes or ratings of personal control regarding dietary intake.